Hubungan Berat dan Panjang Badan Lahir dengan Tinggi Badan Anak di Puskesmas Pante Ceureumen, Kabupaten Aceh Barat - Dewi, Yusna; Anwar, Sufyan; Wati, Rina; Putri, Enda Silvia (Medan Resource Center, 2024)
This study investigates the relationship between birth weight and birth length with the height of children aged 36-48 months at the Pante Ceureumen Health Center, West Aceh Regency. Utilizing a quantitative approach with a cross-sectional design, data collection occurred between July 24-31, 2023. The sample included 55 mothers who gave birth at the health center three years prior, selected using a total sampling method. Data were gathered through anthropometric measurements and structured interviews with mothers. Statistical analysis revealed no significant relationship between birth weight and the height of children aged 36-48 months, as indicated by a p-value (p > 0.05). Similarly, no significant correlation was found between birth length and the height of children in this age group. These findings highlight the need for regular participation in integrated health services (posyandu) to monitor children’s growth and development. Health workers are also encouraged to increase community engagement by conducting educational outreach programs on stunting prevention and optimal child nutrition practices.